Studi Kualitatif Pelaksanaan Metode Akuntansi Berbasis Akrual Pada Puskesmas Tahunan Setelah Menjadi Badan Layanan Umum Daerah (BLUD) - Yanto Yanto; Afrida Andriastuti (Jurnal Rekognisi Akuntansi, 2019)
The change of the Annual Public Health Center into a BLUD aims to improve its services to the community as a form of implementing the Jepara Regency Government in the health sector, promoting general welfare and preserving the life of the nation. With the change to BLUD, the Annual Health Center is given flexibility in financial management by applying the implementation of the accrual-based accounting method. This type of research is qualitative with a descriptive approach to describe the actual information from the informants. While the types of data used in this study are primary and secondary data. This study aims to determine the implementation of accrual-based accounting methods, obstacles, and factors at the Annual Health Center after becoming a Regional Public Service Agency. Based on the results of the research that has been carried out, it shows that the implementation of the accrual-based accounting method at the Annual Health Center has not been implemented in accordance with Jepara Regent Regulation Number 9 of 2017. interference with the application. While the factors that influence the success of this implementation are internal control, consistency in financial reporting, and smooth access to applications.